Nonstoichiometry, structure and properties of nanocrystalline oxides, carbides and sulfides. (May 2021) - Valeeva, Albina A.; Rempel, Andrey A.; Rempel, Svetlana V.; Sadovnikov, Stanislav I.; Gusev, Aleksandr I.
Abstract : The results of recent experimental studies of the influence of the size of oxide, carbide and sulfide nanoparticles on changes in their nonstoichiometry are analyzed and generalized. In relation to intrinsically nonstoichiometric titanium oxides and niobium and vanadium carbides, on the one hand, and stoichiometric silver sulfides, on the other hand, it is shown that a decrease in the particle size to the nano scale has a strong impact on the chemical composition of nanocrystalline compounds, viz ., it leads to the occurrence of or increase in nonstoichiometry. A conclusion is drawn that interplay between the particle size and nonstoichiometry is common to all solid nanocrystalline substances and should be taken into account in studies on the synthesis, structure and properties of these systems. The bibliography includes 260 references.